Socialização organizacional de pessoas com deficiência em uma instituição federal de ensino supeior - Santos, Maria do Socorro Martins dos (2018)
Throughout history, people with disabilities have been victims of prejudice. Today, the labor market has opened doors for this group. Taking as a presupposition the increase in the admission of people with disabilities within organizations, the present research has as general objective to analyze the perceptions of the PCDs on the process of organizational socialization in a Federal Institution of Higher Education. The universe of this research is composed of 114 people with disabilities, who work for the IFES under survey, from which a sample of 15 workers was selected for their disability condition and, for convenience, according to the availability and acceptance of those workers to participate in the study. For this work the qualitative format was adopted and a case study was carried out, taking as reference the theoretical model adapted from Chao et al. (1994), Taormina (1997) and Borges et al. (2010) that culminated in the areas: engagement with the institution; integration with people; and future perspectives. For the collection of data, a script of semi-structured interviews was used and the content analysis was performed through the software Atlas Ti, version 8.0. The results indicated that there was an increase in the number of people with disabilities within the institution, that the people who are entering have a high qualification and intend to continue to improve, but also showed that there are still many difficulties related to accessibility in its most different forms: architectural, technological, attitudinal, informational, communicational, linguistic, etc. Overall, it has been noted that many advances have occurred but that people with disabilities still encounter many difficulties relating mainly to the working conditions in the IFES. Keywords: